Advances in the interrelated nature of vaginal microecology, HPV infection, and cervical lesions - Cui, Mingyu; Wu, Yishi; Liu, Zongyu; Liu, Yunfei; Fan, Limei (Frontiers in Cellular and Infection Microbiology, 2025)
Vaginal microecology serves as a crucial defense mechanism in women’s reproductive health. It encompasses vaginal anatomy, microbial flora, endocrine regulation, and immune responses. Lactobacillus species dominate this ecosystem, maintaining a dynamic balance essential for vaginal health. Studies have highlighted a strong association between vaginal microecology, human papillomavirus (HPV) infection, and cervical lesions. A well-balanced vaginal microenvironment enhances mucosal barriers and immune function, aiding in HPV prevention and clearance. Conversely, disruptions in vaginal microecology compromise these defenses, increasing susceptibility to HPV infection. Persistent high-risk HPV (HR-HPV) infections are key contributors to cervical lesions and may further destabilize the vaginal microbiota(VMB). Additionally, cervical lesion progression is influenced by local immune responses, with HPV infection potentially accelerating disease development by suppressing cervical immunity. This review explores the intricate association between vaginal microecology, HPV infection, and cervical lesions, offering insights into early diagnosis, prevention, and treatment strategies.